2005
DOI: 10.1634/stemcells.2004-0306
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neurodevelopmental Markers by Cultured Porcine Neural Precursor Cells

Abstract: Despite the increasing importance of the pig as a large animal model, little is known about porcine neural precursor cells. To evaluate the markers expressed by these cells, brains were dissected from 60-day fetuses, enzymatically dissociated, and grown in the presence of epidermal growth factor, basic fibroblast growth factor, and platelet-derived growth factor. Porcine neural precursors could be grown as suspended spheres or adherent monolayers, depending on culture conditions. Expanded populations were bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
52
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 35 publications
12
52
0
2
Order By: Relevance
“…In addition to nestin, a number of other markers have been associated with NS and progenitor cells. This study shows expression of NogoA, DCX, Cyclin D2, CD133, Hes1, Oct4, Desmin, CD-90, Nanog and Sox2 (Figure 2a-l), some of which have been reported as expressed by CNS precursor cells, or subsets thereof (Cai et al, 2002;Schwartz et al, 2003 and2005). The expression of these markers ( Figure 2a-l) by porcine NS cells argues for an important role for these genes in the neural development of large mammals.…”
Section: R E T R a C T E Dmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition to nestin, a number of other markers have been associated with NS and progenitor cells. This study shows expression of NogoA, DCX, Cyclin D2, CD133, Hes1, Oct4, Desmin, CD-90, Nanog and Sox2 (Figure 2a-l), some of which have been reported as expressed by CNS precursor cells, or subsets thereof (Cai et al, 2002;Schwartz et al, 2003 and2005). The expression of these markers ( Figure 2a-l) by porcine NS cells argues for an important role for these genes in the neural development of large mammals.…”
Section: R E T R a C T E Dmentioning
confidence: 64%
“…NS cells (Gage, 2000;Jiang et al, 2002) can be cultured over the long term and are able to self-renew and differentiate into neurons, astrocytes and oligodendrocytes when exposed to cytokines in vitro Weiss, 1992 and1996;Schwartz et al, 2005). Thus, the NS cell is one type of well-defined somatic stem cell that can proliferate and differentiate in vitro.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…In the damaged brain, adult neurogenesis is also found in the neocortex, striatum, amygdala and substantia nigra (Gould, 2007) where AQP4 has a high level of expression. Finally, it is reported that AQP4 is the main subtype of aquaporin in adult neural stem cells (ANSCs) (Cavazzin et al, 2006;La Porta et al, 2006;Schwartz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anatomical considerations, we have recently reported that the gene expression profile of cultured porcine forebrain progenitor cells more closely resembles that of the analogous human cells than that of the mouse [16]. This raises the question of whether progenitor cells can also be cultured from the pig retina and, if so, whether the gene expression of these cells resembles their human counterparts [17,18] more than the analogous mouse cells [10].…”
Section: Introductionmentioning
confidence: 99%